DAMPAK PENERAPAN SERVICE EXCELLENCE TERHADAP TINGKAT KEPUASAN NASABAH BANK SYARIAH - Lutfia, Lutfia Sobaroh; Haryanti, Peni (J-EBI Jurnal Ekonomi dan Bisnis Islam, 2026)
This study aims to analyze the impact of implementing service excellence on the level of satisfaction of Islamic bank customers through a literature review approach. The research was conducted by reviewing various journals, books, and scientific reports that discuss service quality, dimensions of service excellence, and customer satisfaction in the context of Islamic banking. The results of the study show that the implementation of service excellence including responsiveness, reliability, assurance, empathy, and physical evidence consistently contributes positively to increased customer satisfaction. Fast, professional, and Sharia-compliant services have been proven to increase customer trust and comfort. However, some literature indicates that challenges remain, particularly regarding human resource quality, service consistency, and digital technology development. Therefore, improving employee competence and service innovation are important strategies for strengthening Islamic bank customer satisfaction.